Suicide rates across income levels: Retrospective cohort data on 1 million participants collected between 2003 and 2013 in South Korea - Sang-Uk Lee (Journal of Epidemiology, 2017)
Background: The relation of income and socioeconomic status with suicide rates remains unclear. Most previous studies have focused on the relationship between suicide rates and macroeconomic factors (e.g., economic growth rate). Therefore, we aimed to identify the relationship between individuals' socioeconomic position and suicide risk.